Visual function of red staminal filaments in a bee-pollinated plant. (13th June 2022) - Hu, Ya-Li; Chen, Zhe; Zhao, Jian-Jun; Niu, Yang; Xu, Gang
ABSTRACT: Background: Floral colour is a primary signal in plant-pollinator interactions. Presumably because bees lack red receptors, bee-pollinated flowers are rarely red. Hypericum (Hypericaceae) is a genus, with yellow flowers and filaments, mainly pollinated by bees. However, one species, H. ascyron exhibits unique red filaments. Aims: We tested whether the red filaments influence pollinator visitation frequency and colour perception. Methods: We examined whether H. ascyron require pollinators for seed set and compared insect visitation rates of H. ascyron with those of a sympatric yellow-filamented congener. Colour perception by bees was also estimated. Results: Pollinator visitation substantially enhanced seed set under natural conditions and flowers of H. ascyron had similar rates of visitation by bees as their yellow-filamented congener. Red filaments per se absorbed ultraviolet light and therefore should not be perceived as a chromatic colour by bees. The chromatic contrasts between filaments and petals as perceived by pollinators was similar between species, whereas achromatic contrasts were higher in H. ascyron . Conclusions: Pure-red staminal filaments work as well in attracting potential pollinators as the yellow filaments of congeners. Based on our findings, we suggest that the evolution of red filament colour may have been driven by factors other than pollinator attraction.